Dig in! - Prince, April Jones; Berg, Michelle (New York : Abrams Appleseed, 2013)
Construction mice don their hard hats to operate construction vehicles--with parts the reader can move--as they complete a big project.
Companion to: Dive in!
Keywords: Board books; Toy and movable books -- Specimens; Stories in rhyme; Construction equipment -- Fiction; Mice -- Fiction; Pizza -- Fiction